The Impact of Social Media on Social Cohesion in South Africa - Matema, Tawanda; Kariuki, Paul (Journal of Economics and Behavioral Studies, 2022)
Social cohesion is an important policy issue with social, political and economic consequences in South Africa. Given the country’s diverse population comprised of different races, ethnicities and migrants from around the world, its history of violence and the persistent incidences of xenophobia, social cohesion has become a prominent issue. The study foregoes discussing the challenges of achieving social cohesion to examine the nexus between social media and social cohesion promotion. Since lockdown was introduced in March 2020, social media has become a means for daily communication, bridging racial, ethnic, class and geographical boundaries. Against this background, this study explored the impact of social media on social cohesion in South Africa? The main objective was to examine the role played by social media in fostering social cohesion. A systematic review of relevant academic literature and research reports on social media and social cohesion was adopted in gathering data. By examining the social media social cohesion nexus, an illustration of social media as an essential determinant of social cohesion can be delineated. Teasing out these aspects is vital in enriching the current literature on understanding social cohesion. The study found that social media has become an essential platform for nation-building, potentially bridging racial, ethnic, cultural, and geographical gaps in South African society. However, due to the threats of misinformation and insensitive use, social media can hamstring social cohesion and cause instability. The study recommends that social media be used appropriately and sensitively in strengthening interpersonal relationships that transcend race, culture, ethnicity, nationality, and religion.